PENGARUH CADANGAN KERUGIAN PIUTANG TERHADAP PROFITABILITAS PERUSAHAAN - Dewi, Anita Puspa; Warisi, Darwin; Desmon, Desmon (Universitas Mitra Indonesia, 2023)
AbstractThis study aims to find out and analyze 1) how much influence the allowance for losses on receivables has on profitability, 2) to determine the significance level of reserves for losses on receivables on profitability, 3) to find out whether company policy through credit sales has an effect on the high or low profitability of the company. The population in this study is the financial statements of automotive companies that have been audited and published on the Indonesia Stock Exchange (IDX). The sampling technique uses a purposive sampling method so that a sample of 9 companies is obtained. As for the results, there is no effect of reserves for losses on receivables on ROA. Keywords: allowance for losses on receivables, Profitability, ROA AbstrakPenelitian ini bertujuan untuk mengetahui dan menganalisis 1) seberapa besar pengaruh cadanga kerugian piutang terhadap profitabilitas, 2) untuk mengetahui tingkat signifikansi cadangan kerugian piutang terhadap profitabilitas, 3) untuk mengetahui apakah kebijakan perusahaan melalui penjualankredit berpengaruh terhadap tinggi rendahnya profitabilitas perusahaan. populasi dalam penelitian ini adalah laporan keuangann perusahaan otomotif yang telah diaudit dan di publiskasikan di Bursa Efek Indonesia (BEI), tknik sampling menggunakan metode purposive sampling sehingga di peroleh sampel sebanyak 9 perusahaan. adapun hasil tidak terdapat pengaruh cadangan kerugian piutang terhadap ROA . Kata kunci: cadangan kerugian piutang, Profitabilitas, ROA